Highly Efficient Synthesis of Glucose Fatty Acid Esters Catalyzed by High Performance Lipase Preparations - Arora, Benu (Asian Journal of Chemistry, 2021)
Glucose fatty acid esters were synthesized using cross-linked enzyme aggregates (CLEAs), protein coated microcrystals (PCMCs) and cross-linked protein coated microcrystals (CLPCMCs) of Candida antarctica lipase B (CALB) as biocatalyst designs in single and mixed solvent systems. Up to 90% conversion and more than 99% regioselectivity were obtained using vinyl acetate as the acyl donor in a solvent system composed of 2-methyl-2-butanol (2M2B) and 30% (v/v) DMSO, with CALB CLEAs within 45 min. Similar results were obtained with CALB CLPCMCs as the biocatalyst under the same reaction conditions. This approach was then extended to the synthesis of glucose esters with higher acyl chain length. The synthetic strategy used in this work can potentially be extended for the fast and regioselective esterification/transesterification of other sugars as well.